Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

solve:-

Asked by Abhishek Kumar Singh 16th October 2013, 12:16 PM
Answered by Expert
Answer:

abx2-(a+b)2(x-1)=0

abx2-(a+b)2x+(a+b)2=0

Using quadratic formula,

B2-4AC=(a+b)4-4ab(a+b)2

=(a+b)2[(a+b)2-4ab]

=(a+b)2(a2+b2+2ab-4ab)

=(a+b)2(a-b)2

So, sqrt (B2-4AC)=(a+b)(a-b) =(a2-b2)

x=[(a+b)2 (a2-b2)]/2ab

x=[a2+b2+2ab(a2-b2)]/2ab

x=(a+b)/b  or  x=(a+b)/a

Answered by Expert 16th October 2013, 12:29 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp